CODE OF ETHICS URGENCY IN THE IMPLEMENTATION OF GENERAL ELECTION IN INDONESIA - Jeremia Alexander Wewo; Kotan Y. Stefanus; Umbu Lili Pekuwali (Jurnal Dinamika Hukum, 2018)
The mirror of state of democracy is election. Three institutions that organize General Election include General Election Commission, Election Supervisory Agency and Election Organizer Ethics Council. This study applies normative legal method. Code of Ethics constitutes significant meaning in every General Election for governing the General Election organizer to have integrity and high dedication. Code of Ethics and law in general election are inseparable; Code of Ethics is the guidelines for the election organizer to act and behave while the law is the foundation of a General Election implementation. In order to realize a democratic and quality General election then a General election process must be based on Code of Ethics and law.Keywords: General election, election organizer, Code of Ethics, law